2019
DOI: 10.1101/736652
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tritrophic interactions involving a dioecious fig tree, its fig pollinating wasp and fig nematodes

Abstract: 24 25 Many species of fig trees (Ficus spp., Moraceae) have nematodes that develop 26 inside their inflorescences (figs). Nematodes are carried into young figs by females of the 27 trees' host-specific pollinating fig wasps (Agaonidae) that enter the figs to lay their eggs. 28 The majority of Asian fig trees are functionally dioecious. Pollinators that enter figs on 29 female trees cannot reproduce and offspring of any nematodes they carry will also be 30 trapped inside. The biology of the nematodes is diverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 38 publications
(51 reference statements)
1
3
0
Order By: Relevance
“…Most research on nematodes in dioecious fig trees has concentrated on male trees that generate new generations of fig wasps [32,36]. The nematode life cycles in F. hispida figs were mainly similar to those previously described in male figs of other fig trees of both dioecious and monoecious species [4,14,37,38]. However, our research demonstrated that nematodes associated with F. hispida can grow and reproduce within figs from female trees, as shown by a recent study in China [39].…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Most research on nematodes in dioecious fig trees has concentrated on male trees that generate new generations of fig wasps [32,36]. The nematode life cycles in F. hispida figs were mainly similar to those previously described in male figs of other fig trees of both dioecious and monoecious species [4,14,37,38]. However, our research demonstrated that nematodes associated with F. hispida can grow and reproduce within figs from female trees, as shown by a recent study in China [39].…”
Section: Discussionsupporting
confidence: 82%
“…The Five to six figs from each tree, including their contents, were then placed separately in a Baermann extraction funnel using a method described previously [29] and adjusted later [14]. Each fig was later cut into eight pieces and set on a fine fabric sheet before being submerged in 60 mL distilled water.…”
Section: Sampling Methods and Fig Extractionmentioning
confidence: 99%
See 2 more Smart Citations